2003
DOI: 10.1074/jbc.m212540200
|View full text |Cite
|
Sign up to set email alerts
|

Congo Red Populates Partially Unfolded States of an Amyloidogenic Protein to Enhance Aggregation and Amyloid Fibril Formation

Abstract: Congo red (CR) has been reported to inhibit or enhance amyloid fibril formation by several proteins. To gain insight into the mechanism(s) for these apparently paradoxical effects, we studied as a model amyloidogenic protein, a dimeric immunoglobulin light chain variable domain. With a range of molar ratios of CR, i.e. r ‫؍‬ [CR]/[protein dimer], we investigated the aggregation kinetics, conformation, hydrogen-deuterium exchange, and thermal stability of the protein. In addition, we used isothermal titration c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 54 publications
6
79
2
Order By: Relevance
“…Congo red appeared to stabilize the hA oligomers, blocking both their lateral and longitudinal growth into mature fibrils, with inhibition of the former process occurring only in part. The inhibitory effect of Congo red is generally consistent with the literature (13,30,37,38), but not when it comes to details of the mechanism. Podlisny et al (37) reported that Congo red stabilized amyloid-␤ monomers before they formed oligomers.…”
Section: Discussionsupporting
confidence: 78%
“…Congo red appeared to stabilize the hA oligomers, blocking both their lateral and longitudinal growth into mature fibrils, with inhibition of the former process occurring only in part. The inhibitory effect of Congo red is generally consistent with the literature (13,30,37,38), but not when it comes to details of the mechanism. Podlisny et al (37) reported that Congo red stabilized amyloid-␤ monomers before they formed oligomers.…”
Section: Discussionsupporting
confidence: 78%
“…Similar to the perinuclear location of the aggresomes in CryAB R120G -transfected cardiomyocytes, Congo red staining was restricted largely to the perinuclear region. There are conflicting data with respect to the ability of Congo red to interfere with or enhance amyloid fibril formation, but a recent study (28) showed that although low concentrations led to enhanced fibril formation, high concentrations inhibited the process effectively. Continuous treatment of the cells with high concentrations of the dye prevented aggresome formation effectively, and no Congo red-positive bodies could be observed in the cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By itself, resveratrol is a potent anti-oxidant which is thought to be responsible for the French Paradox [65]; relating to the low incidence of cardiovascular disease in a French population with high intake of saturated fats. In addition to its demonstrated capacity to inhibit (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) fibril formation in vitro [16], resveratrol is also capable of promoting intracellular uptake and degradation of through a proteosome-dependent mechanism [66] and protecting against -induced neurotoxicity [67,68], possibly through activation of the NAD-dependent histone deacetylase, SIRT1 [69]. In the present study using the ELISA-based assay, catechin showed no inhibitory activity during the early stages of oligomerization, whereas rosmarinic acid demonstrated some activity at the highest concentration tested.…”
Section: Discussionmentioning
confidence: 99%
“…While the identity of a number of oligomerization inhibitors have been reported, few address the stoichiometric relationship between inhibitor and peptide, and when calculated, suggest inhibitor to peptide ratios of no greater than one, or in some cases less than one [26][27][28][29][30][31][32]. Presuming that inhibitors must physically bind to peptide to prevent oligomerization [33,34], it is difficult to imagine a mechanism of action where inhibitor to peptide ratios are less than 1.…”
Section: Introductionmentioning
confidence: 99%